To what extent does self-reported physical activity impact children's wellbeing and mental health? Insights from school-aged children in Wales. - Michaela James; Mary Adebayo; Mayara Silveira Bianchim; Levi Hughes; Marianne Mannello; Emily Marchant; Sinead Brophy (PLoS ONE)
There has been emphasis on the wellbeing of school-aged children amongst research, policy and practice in recent years, particularly during key developmental stages such as early childhood and adolescence. This study aimed to identify specific factors of self-reported physical activity that are associated with wellbeing and mental health among school-aged children in Wales. Using data from the Health and Attainment of Pupils in Primary Education in Wales (HAPPEN-Wales) cohort, this study analysed survey responses from 16,731 children aged 7-11 collected between 2016 and 2022. The HAPPEN survey includes self-reported measures of physical activity, physical literacy, sedentary behaviour, wellbeing, mental health, and local community environment. Wellbeing and mental health were assessed using the Good Childhood Index and the Me and My Feelings Questionnaire. Physical literacy was captured through questions on motivation, confidence, competence, and understanding of physical activity benefits. Additional data on environmental factors and socioeconomic status were also considered. Multiple regression and decision tree analyses were used to examine factors associated with overall wellbeing. Key factors associated with good wellbeing included being more physically active (Coef.:0.17 [95%CI: 0.05 to 0.29]), being less sedentary (Coef.: -0.16 [95%CI: -0.28 to -0.05]), feeling confident to take part in lots of physical activity (Coef.: 0.35 [95%CI: 0.16 to 0.55]), feeling good at lots of physical activity (Coef.: 0.30 [95%CI:0.14 to 0.46], having less knowledge around understanding (Coef.: -0.29 [95%CI: -0.57 to -0.07]), feeling safe (Coef.: 0.77 [95%CI: 0.66 to 0.89]), autonomous (Coef.: 0.57 [95%CI: 0.40 to 0.73]) and competent (Coef.: 0.51 [95%CI: 0.35 to 0.67]). The findings highlight the importance of providing opportunities for children to develop their confidence, competency and to feel like they have a choice in their lives. This may be done by providing safe, engaging, and varied physical activity opportunities in schools and communities to support children's overall wellbeing.